The role of TIM-3 in sepsis: a promising target for immunotherapy? - Wang, Changli; Liu, Jinhai; Wu, Qi; Wang, Zhi; Hu, Baoji; Bo, Lulong (Frontiers in Immunology, 2024)
Sepsis remains a significant cause of mortality and morbidity worldwide, with limited effective treatment options. The T-cell immunoglobulin and mucin domain-containing molecule 3 (TIM-3) has emerged as a potential therapeutic target in various immune-related disorders. This narrative review aims to explore the role of TIM-3 in sepsis and evaluate its potential as a promising target for immunotherapy. We discuss the dynamic expression patterns of TIM-3 during sepsis and its involvement in regulating immune responses. Furthermore, we examine the preclinical studies investigating the regulation of TIM-3 signaling pathways in septic models, highlighting the potential therapeutic benefits and challenges associated with targeting TIM-3. Overall, this review emphasizes the importance of TIM-3 in sepsis pathogenesis and underscores the promising prospects of TIM-3-based immunotherapy as a potential strategy to combat this life-threatening condition.